DETERMINANTS OF SOCIAL EXCLUSION AMONG OLD WOMEN: A CASE STUDY OF GUJRAT, PAKISTAN - Mehwish Mobeen, Dr. Muhammad Shabbir, Dr. Sadaf Mahmood, Tariq Mehmood Bhuttah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of research is to analyze the causes of social exclusion among old women in District Gujrat, Punjab, Pakistan. Different factors like social setup, low education and poor health cause of older women exclusion. Quantitative research approach was used to complete this research and the researcher constructed the interview schedule for data collection. Respondent in this research was the old women having the age above 45 years and purposive sampling technique was used to draw a sample size from the target population. The sample size was 300 old women having age 45 years and above. The researcher used the Pearson correlation and regression analysis to analyze the relationship between these variables. The results of the correlation and regression analysis indicated a positive and significant association between independent variables (social setup, low education and poor health) and dependent variables (old women exclusion). The study concluded that family social setups, lower level of education and poor health conditions are caused of old women exclusion because in patriarchal societies women have very limited resources for survive in a society that the reason women are excluded by every field of life. So, Women should be treated as equals to men and these factors should be eliminated, which requires a lot of effort from every member of society.